Osteoporosis Awareness, Self-Efficacy and Health Beliefs Among Staff in an Obstetrics and Gynecology Hospital: A Cross-Sectional Study - Zhou Y; Xu Z; Zhang Z; Su J (Risk Management and Healthcare Policy)
Yun Zhou,1,* Zheyun Xu,2,* Zhifen Zhang,3 Jun Su4,5 1Outpatient Department, Hangzhou Women’s Hospital (Hangzhou Maternity and Child Health Care Hospital), Hangzhou, Zhejiang, 310008, People’s Republic of China; 2The Fourth Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China; 3Department of Obstetrics and Gynecology, Hangzhou Women’s Hospital (Hangzhou Maternity and Child Health Care Hospital), Hangzhou, Zhejiang, 310008, People’s Republic of China; 4School of Public Health, Hangzhou Normal University, Hangzhou, 311121, People’s Republic of China; 5Intensive Care Medicine Department, Hangzhou Women`s Hospital (Hangzhou Maternity and Child Health Care Hospital), Hangzhou, 310008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Su, Email junjunsu@163.comBackground: We investigated the key factors that influence the awareness, health beliefs, and self-efficacy of osteoporosis among the staff of an obstetrics and gynecology hospital to identify the key target population for carrying out education and promotion in medical institutions, hoping to improve women’s awareness and prevention and treatment consciousness of osteoporosis from the source.Methods: A cross-sectional study was conducted from October 15 to October 24 in 2023, and 200 staff members were randomly sampled from an obstetrics and gynecology hospital in Hangzhou city for a questionnaire survey. We used a quantile regression model to analyze the key factors influencing the scores of each item.Results: The study results showed that undergraduate degree or above, working as a doctor, work experience of < 5 years or 10– 20 years and high professional technical title are related to a higher level of osteoporosis knowledge. Male gender was associated with higher exercise efficacy and calcium barriers scores. Older age and long years of working experience were associated with higher susceptibility score. Lower education level was associated with higher calcium barriers score. Doctor occupation was associated with lower seriousness score, higher exercise benefits score, higher calcium benefits scores and higher health motivation score. Professional and technical title was also related to exercise and calcium benefits score.Conclusion: When carrying out education and promotion work on osteoporosis prevention and treatment targeting the group of healthcare workers, different content and emphases should be considered, and different groups should be selected for more targeted publicity and popularization.Keywords: obstetrics and gynecology hospital, osteoporosis, awareness, health belief, self-efficacy